Extracellular nucleotides as novel, underappreciated pro-metastatic factors that stimulate purinergic signaling in human lung cancer cells. Issue 1 (December 2015) - Schneider, Gabriela; Glaser, Talita; Lameu, Claudiana; Abdelbaset-Ismail, Ahmed; Sellers, Zachariah; Moniuszko, Marcin; Ulrich, Henning; Ratajczak, Mariusz
Abstract Background One of the challenging problems of current radio-chemotherapy is recurrence and metastasis of cancer cells that survive initial treatment. We propose that one of the unwanted effects of radiochemotherapy is the release from damaged ("leaky") cells of nucleotides such as ATP and UTP that exert pro-metastatic functions and can directly stimulate chemotaxis of cancer cells. Methods To address this problem in a model of human lung cancer (LC), we employed several complementaryin vitro andin vivo approaches to demonstrate the role of extracellular nucleotides (EXNs) in LC cell line metastasis and tumor progression. We measured concentrations of EXNs in several organs before and after radiochemotherapy. The purinergic receptor agonists and antagonists, inhibiting all or selected subtypes of receptors, were employed inin vitro andin vivo pro-metastatic assays. Results We found that EXNs accumulate in several organs in response to radiochemotherapy, and RT-PCR analysis revealed that most of the P1 and P2 receptor subtypes are expressed in human LC cells. EXNs were found to induce chemotaxis and adhesion of LC cells, and an autocrine loop was identified that promotes the proliferation of LC cells. Most importantly, metastasis of these cells could be inhibited in immunodeficient mice in the presence of specific small molecule inhibitors of purinergic receptors. Conclusions Based on this result, EXNs are novel pro-metastatic factors released particularly during radiochemotherapy, and inhibition of their pro-metastatic effects via purinergic signaling could become an important part of anti-metastatic treatment.